Evolution and economic significance of listwaenites associated with Neoproterozoic ophiolites in South Eastern Desert, Egypt - M.K. AZER (Geologica Acta, 2013)
Most South Eastern Desert ophiolites are found along the Allaqi-Heiani-Gerf suture along the Egypt-Sudan border. Serpentinites, altered slices of upper mantle, are the main components of this suture and other sutures in the Arabian-Nubian Shield. Listwaenites are a distinctive alteration of serpentinized peridotite and are commonly found in shear zones that concentrate hydrothermal fluids involved in the formation of this type of rock. Along Wadi Allaqi area, listwaenites are distinguished into two main types: i) silica-rich, and ii) carbonate-rich. The presence of fuchsite in the former indicates that it is typical listwaenite, while the absence of fuchsite in the latter indicates listwaenite-like rock. These two types of listwaenites represent different stages of hydrothermal alteration. The large variations in their mineralogical and geochemical compositions are due to the different influence of reactions between protoliths and hydrothermal solutions, leading to different stages of metasomatic replacement. Ore minerals accompanying the listwaenites vary greatly both among and within separate occurrences. These variations depend on lots of factors, including the presence of shearing, P-T conditions, reactions with host rocks, and the composition of the hydrothermal fluids. Silica-rich listwaenite is well sheared and is more commonly ore bearing, while carbonate-rich listwaenite is less obviously sheared and shows less metal enrichment. The listwaenites of Wadi Allaqi area have a potential for gold mineralization (4-12ppm; 400-1100x enriched in comparison with serpentinites) since native gold occurs as inclusions in pyrite or as small disseminated specks along fractures. Base metals, mostly copper, lead and zinc, are also associated with listwaenites, but are more erratically distributed. Gold content increases with increasing SiO2 content of listwaenite. Carbonatization and silicification of ophiolitic peridotites can concentrate gold in the alteration products more than the parent rocks.